(untitled) (Philological Studies, 2019)
The article aims to present the educational histories in the Vardar part of Macedonia between the two world wars. The school system in the Vardar Macedonia was under the jurisdiction of the Ministry of Education of the Kingdom of Yugoslavia. The main issue presented before this Ministry was illiteracy, that is to say that the population did not speak Serbian as its official language. Education was just a thread through which the Serbian regime conducted policy assimilation and the denationalization of Macedonians in Vardar Macedonia.